(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study presents a comprehensive analysis of the daily life, biological health, and diet of the Bronze Age Sopolli culture population, based on paleoanthropological, archaeobotanical, and archaeozoological evidence collected from excavations since the 1970s. The study examines skeletal and dental remains to evaluate disease patterns, trauma, and nutritional habits. In addition, the analysis considers the socio-economic context, including domestic livestock, wild animals, and cultivated crops, to reconstruct the dietary and occupational practices of the population. These findings contribute to understanding the health status, mortality patterns, and social organization of the Sopolli culture in Southern Uzbekistan.